Mechanism of Resistance to Glyphosate in Lolium perenne from Argentina - Yanniccari, Marcos; Gómez-Lobato, María E.; Istilart, Carolina; Natalucci, Claudia; Giménez, Daniel O.; Castro, Ana M. (Frontiers in Ecology and Evolution, 2017)
In Argentina, glyphosate resistance was reported in a Lolium perenne population after 12 years of successful herbicide use. The aim of the current paper was to put in evidence for the mechanism of glyphosate resistance of this weed. Susceptible leaves treated with different doses of glyphosate and incubated in vitro showed an accumulation of shikimic acid of around three to five times the basal level, while no changes were detected in leaves of glyphosate-resistant plants. The resistance mechanism prevents shikimate accumulation in leaves, even under such tissue-isolation conditions. The activity of the glyphosate target enzyme (EPSPS: 5-enolpyruvylshikimate-3-phosphate synthase) was quantified at different herbicide concentrations. EPSPS from resistant plants showed no difference in glyphosate-sensitivity compared to EPSPS from susceptible plants, and, accordingly, no amino acid substitution causing mutations associated with resistance were found. While the glyphosate target enzymes were equally sensitive, the basal EPSPS activity in glyphosate resistant plants was approximately three-fold higher than the EPSPS activity in susceptible plants. This increased EPSPS activity in glyphosate resistant plants was associated with a 15-fold higher expression of EPSPS compared with susceptible plants. Therefore, the over-expression of EPSPS appears to be the main mechanism responsible for resistance to glyphosate. This mechanism has a constitutive character and has important effects on plant fitness, as recently reported.